Superficial siderosis: Case report and literature review - Kresojević Nikola D.; Petrović Igor N.; DragaševićMišković Nataša T.; Kostić Vladimir S. (Srpski Arhiv za Celokupno Lekarstvo, 2013)
Introduction. Superficial siderosis (SS) is caused by chronic subarachnoid bleeding and is characterized by free iron and hemosiderin deposition along the pial and subpial structures of central nervous system. SS leads to progressive and irreversible CNS damage. The most common causes of chronic subarachnoidal bleeding are tumors, head and spinal cord trauma, arteriovenous malformations and aneurysms. SS is characterized by clinical triad: sensorineural hearing loss, cerebellar ataxia and piramydal signs. Brain MR imaging is the investigation of choice for the diagnosis of SS. Typical findings include hypointensities seen on T2weighted MR imaging around the brain, cerebellum, brain stem, spinal cord, VIII cranial nerve and atrophy of cerebellum and medulla. Case Outline. A 71-yearold female patient noticed hand tremor in the middle of the third decade of life, and later slowly progressive bilateral hearing loss. At the age of 64 she developed un steady gate, hand clumsiness and dysarthria, to became incapable of independent walking and standing five years later. Clinical course and brain MRI findings were typical for SS, but additional investigation did not reveal the couse of subarahnoidal bleeding. Conclusion. SS represents a rare and underrecognized condition that must be considered in all patients with cerebellar syndrome of unknown cause. Early diagnosis of SS in some cases with identified cause of chronic bleeding allowes therapeutic interventions that may prevent further progression of the disease. [Projekat Ministarstva nauke Republike Srbije, br. 175090]